Fogging with antibrowning agents as an alternative to conventional immersion treatments to extend shelf life of mushrooms - Ojeda, Gonzalo Adrián (2020)
Fil: Ojeda, Gonzalo Adrian. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas Naturales y Agrimensura; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.